2011
DOI: 10.1111/j.1469-8137.2011.03852.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the ceramide synthase LOH1 causes spontaneous cell death inArabidopsis thaliana

Abstract: Summary• The bioactive lipid ceramide is produced by the enzyme ceramide synthase, which exists in several isoforms in most eukaryotic organisms. Here, we investigated functional differences between the three ceramide synthase isoforms in Arabidopsis thaliana.• The biochemical properties of the three ceramide synthases were investigated by comparing lipid profiles of yeast strains expressing LOH1, LOH2 or LOH3 with those of wild-type and loh1, loh2 and loh3 knockout plants. Expression profiles of the ceramide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
134
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(148 citation statements)
references
References 54 publications
(109 reference statements)
11
134
0
Order By: Relevance
“…Recent studies have shown that the Lag1/Lac1 components of the S. cerevisiae ceramide synthase are phosphorylated by Ypk1, and this phosphorylation stimulates ceramide synthase activity in response to heat and reduced intracellular sphingolipid levels (Muir et al, 2014). This finding points to possible coordinated regulation of ORM-mediated SPT and ceramide synthase activities to regulate sphingolipid homeostasis, which is likely more complicated in plants and mammals due to the occurrence of functionally distinct ceramide synthases in these systems (Stiban et al, 2010;Markham et al, 2011;Ternes et al, 2011;Luttgeharm et al, 2016).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies have shown that the Lag1/Lac1 components of the S. cerevisiae ceramide synthase are phosphorylated by Ypk1, and this phosphorylation stimulates ceramide synthase activity in response to heat and reduced intracellular sphingolipid levels (Muir et al, 2014). This finding points to possible coordinated regulation of ORM-mediated SPT and ceramide synthase activities to regulate sphingolipid homeostasis, which is likely more complicated in plants and mammals due to the occurrence of functionally distinct ceramide synthases in these systems (Stiban et al, 2010;Markham et al, 2011;Ternes et al, 2011;Luttgeharm et al, 2016).…”
mentioning
confidence: 98%
“…Class I ceramide synthase activity resulting from the Longevity Assurance Gene One Homolog2 (LOH2)-encoded ceramide synthase acylates, almost exclusively, LCBs containing two hydroxyl groups (dihydroxy LCBs) with 16:0-CoA to form C16 ceramides, which are used primarily for GlcCer synthesis Ternes et al, 2011;Luttgeharm et al, 2016). Class II ceramide synthase activities resulting from the LOH1-and LOH3-encoded ceramide synthases are most active in the acylation of LCBs containing three hydroxyl groups (trihydroxy LCBs) with VLCFA-CoAs, including primarily C 24 and C 26 acyl-CoAs Ternes et al, 2011;Luttgeharm et al, 2016). Class II (LOH1 and LOH3) ceramide synthase activity is essential for producing VLCFA-containing glycosphingolipids to support the growth of plant cells, whereas class I (LOH2) ceramide synthase activity is nonessential under normal growth conditions Luttgeharm et al, 2015b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SA was prepared using MTBE/methanol/water and quantified by LC-MS/ MS according to Ternes et al (2011).…”
Section: Sa Analysismentioning
confidence: 99%
“…The major plant sphingolipids typically contain a C18 aliphatic amino alcohol chain (also called sphingoid long-chain base). The aliphatic amino alcohol chain can be dihydroxylated (d) or trihydroxylated (t) [16,17]. Plant sphingolipids have a fatty acid chain of various lengths (about C14 to C28), but the preponderance of plant sphingolipids has a C16 fatty acid chain [18,19].…”
Section: Introductionmentioning
confidence: 99%